A Blueprint for High Altitude Acclimatization Prior to High Altitude Competition for Professional Athletes - Rashi Ramchandani; Shyla Gupta; Emaad Mohammad; Tereza Florica; Reem Al Rawi; Ricardo Sebastian Galdeano; Jorge Sotomayor-Perales; Adrian Baranchuk (University Library System, University of Pittsburgh, 2024)
Introduction: Among professional athletes, high altitude training is a popular technique due to its documented success on improving cardiovascular health and athletic performance. Nevertheless, there is little consensus on the guidelines for high altitude training and competition. This review sought to summarize existing literature for acclimatization recommendations for competing at high altitudes and suggests a blueprint that could be followed by athletes and trainers.  Methods: This paper is part of the Altitude Nondifferentiated ECG Study (ANDES) project. A non-systematic search was conducted using Pubmed, EMBASE and MEDLINE databases. Results: Six studies were included, all of which recommended a gradual ascent before competition. The duration of acclimatization ranged from 4 days to 2 weeks depending on the magnitude of ascent. Athletes are encouraged to have pre-ascent assessments of ferritin, transferrin, hemoglobin mass, ECG, and weight with close monitoring of adverse altitude-induced complications. Conclusion: This study provides insight on key recommendations for athletes and trainers to consider when training and competing at high altitudes. These strategies can optimize athletic performance and mitigate deleterious altitude effects that can hinder functionality and training.